Combined metal complex and application thereof in fluorescent material

By using fluorescent materials prepared by combining phase change materials such as metal complexes and cellulose in 3D printed wires, the problem of insufficient thermal stability of fluorescent materials is solved, significantly improving the thermal aging and printing performance of fluorescent materials, and reducing the The risk of nozzle blockage improves the stability and efficiency of 3D printing.

CN119264903APending Publication Date: 2025-01-07GUANGXI MODERN VOCATIONAL & TECH COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411394756.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing fluorescent materials lack thermal stability in 3D printed wires, which are prone to decomposition or change properties at high temperatures, resulting in plugging and viscosity changes during printing, affecting printing performance.

Method used

Combined metal complexes are used, including 4f metal complexes [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O and 4f metal complexes [Dy6(MBA)6(OH)4(H2O)8 ](OH)2·33H2O, using 2-hydroxy-3-methoxybenzoic acid as the organic ligand in the multi-coordination mode, combined with phase change materials such as cellulose, prepare fluorescent materials through ultrasonic treatment and vacuum drying to enhance their Thermal stability and durability.

Benefits of technology

It improves the quantum yield and fluorescence lifetime of fluorescent materials, ensures the performance stability of the material under different environmental conditions, reduces the risk of nozzle blockage during 3D printing, and improves printing efficiency and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073444200000071
    Figure BDA0005073444200000071
Patent Text Reader

Abstract

The invention relates to the field of metal complexes, in particular to a combined metal complex and application thereof in a fluorescent material. The combined metal complex disclosed by the invention comprises at least one of a 4f metal complex [Dy3 (HMBA) (MBA) 3 (H2O) 3 (OH) 2]. 10H2O and a 4f metal complex [Dy3 (HMBA) (MBA) 3 (H2O) 3 (OH) 2]. 10H2O. 2-hydroxy-3-methoxybenzoic acid with a multi-coordination mode and fluorescence emission of 380-550 nm is selected as an organic ligand, the ligand contains phenolic hydroxyl groups, carboxylic acid groups and methoxyl groups, and the functional groups can form stable coordination bonds with various metal ions, so that the diversity of coordination and the stability of the complex are improved. Moreover, the ligand can coordinate with a metal center in various modes, including single tooth, double tooth, mu1, 1-bridging, mu1, 3-bridging and the like, and is beneficial to construction of metal complexes with various structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal complexes, in particular to combined metal complexes and applications thereof in fluorescent materials. Background Art

[0002] Metal complexes are compounds formed by ligands and metal atoms or ions through coordination bonds. They are of various types and have unique physical and chemical properties. They are widely used in industrial catalysis, materials science, biomedicine, and analytical chemistry. Some metal complexes also have fluorescent properties.

[0003] The difference between 4f metal complexes and metal complexes is that 4f metal complexes are a subclass of metal complexes, in which the central metal ion is a rare earth metal ion in the 4f region, has a unique electronic structure and physical and chemical properties, and has important applications in luminescent materials, magnetic materials, catalysis and other fields.

[0004] 4f metal complexes are compounds formed by 4f metal ions and ligands through coordination bonds. 4f metal ions usually have a higher charge density and a smaller ionic radius, which makes the coordination between them and the ligands stronger, thus forming a stable complex.

[0005] The luminescence of 4f metal complexes originates from the ff transition or df transition of the central metal ion, which is less affected by the environment and has a long luminescence lifetime. The luminescence mechanism of traditional / ordinary fluorescent materials is diverse. For example, organic fluorescent materials are based on intramolecular transitions and generally have a short luminescence lifetime. 4f metal complexes have sharp emission peaks, narrow half-peak widths and high color purity, and can provide rich luminescence colors. The emission spectrum of traditional fluorescent materials is relatively wide, and the color purity is not as good as that of 4f metal complexes. 4f metal complexes can have high luminescence efficiency under reasonable design, and usually have good thermal stability and chemical stability. The luminescence efficiency of traditional fluorescent materials varies depending on the type. The stability of organic fluorescent materials is relatively poor, and the stability of inorganic fluorescent materials also varies. 4f metal complexes have important applications in biomedicine, display technology, lighting and anti-counterfeiting. Traditional fluorescent materials are widely used in lighting equipment, display devices, coatings, inks and plastics, and occupy a certain market with the advantages of low cost and easy processing.

[0006] CN109721979A discloses a composite material preparation of a fluorescent PLA matrix for 3D printing. It introduces a composite reinforced fluorescent polylactic acid (PLA) and samarium-doped magnesium aluminate phosphor (MgAl2O4:Sm3+) to prepare a bioplastic composite filament for 3D printing applications. The phosphor is modified by 3-aminopropyltriethoxysilane, thereby enhancing the compatibility of PLA and the phosphor, so that the introduction of fluorescent substances into the PLA material can be realized.

[0007] CN110106574A discloses a dual-wavelength fluorescent anti-counterfeiting fiber and a method for manufacturing the same. The invention introduces a dual-wavelength fluorescent anti-counterfeiting fiber, which includes a fiber body made of a molding resin and a luminescent medium dispersed in the molding resin as raw materials, wherein the luminescent medium includes two organic metal complexes, one of which is Eu(TTA)3Phen and the other is Tb(AcAc)3Phen. The europium complex and terbium complex used in the invention are typical organic rare earth complexes, which have good compatibility with the molding resin and can be evenly dispersed in the anti-counterfeiting fiber. The anti-counterfeiting fiber has high luminous intensity and can emit fluorescence of different colors under different excitation lights, and has a good anti-counterfeiting effect.

[0008] In the above inventions, the performance of fluorescent materials when used in polymers as 3D printing wires has not been studied. In the actual application of fluorescent materials, when the thermal stability of fluorescent materials is poor, they may decompose or change their properties under high temperatures, resulting in uneven internal dispersion of the processed wires, which can easily lead to clogging during the printing process. It is also possible that the addition of fluorescent materials may cause changes in the viscosity of the printing materials, resulting in poor flow and clogging. Summary of the invention

[0009] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a combined metal complex as a fluorescent material applied to 3D printing wires, enrich the types of fluorescent materials, and improve the heat aging resistance of fluorescent materials in 3D printing wires.

[0010] To achieve the above objectives, the present invention provides a combined metal complex, comprising at least one of a 4f metal complex [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O and a 4f metal complex [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O.

[0011] The present invention selects 2-hydroxy-3-methoxybenzoic acid with multiple coordination modes and fluorescence emission at 380-550nm as an organic ligand. The ligand contains phenolic hydroxyl, carboxylic acid and methoxy groups. These functional groups can form stable coordination bonds with various metal ions, increasing the diversity of coordination and the stability of the complex. In addition, the ligand can coordinate with the metal center in a variety of modes, including monodentate, bidentate, μ1,1-bridged, μ1,3-bridged, etc., which is helpful for constructing metal complexes with diverse structures.

[0012] Preferably, the combined metal complex is prepared by mixing a 4f metal complex [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O and a 4f metal complex [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O in a mass ratio of 1-3:1-3.

[0013] Preferably, the preparation method of the 4f metal complex [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O is: dissolve 40-80 mg of 2-hydroxy-3-methoxybenzoic acid and 100-150 mg of triethylamine in 2-3 mL of N,N-dimethylformamide; then dissolve 100-150 mg of Dy(NO3)3·6H2O in 2-3 mL of distilled water; mix the above solutions and then stir for 1-3 hours; and obtain block-shaped square colorless crystals by volatilizing the filtrate at room temperature.

[0014] Preferably, the preparation method of the 4f metal complex [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O is: dissolve 40-80 mg 2-hydroxy-3-methoxybenzoic acid and 100-150 mg triethylamine in 1-3 mL N,N-dimethylformamide; then dissolve 300-400 mg Dy(NO3)3·6H2O in 3-6 mL distilled water; mix the above solutions and then stir for 1-3 hours; after the solution is naturally evaporated in the air, rectangular block-shaped colorless crystals are obtained.

[0015] The present invention selects 2-hydroxy-3-methoxybenzoic acid with a multi-coordination mode and a fluorescence emission at 380-550nm as an organic ligand. In addition, the 2-hydroxy-3-methoxybenzoic acid ligand reacts with Dy(III) to form a Dy(III)3 triangular vortex magnet similar to that based on o-vanillin, and the carboxyl group can also be μ 1,3 -Bridging mode connects multiple coupled Dy(III)3 triangle units.

[0016] The invention also discloses the application of the combined metal complex in fluorescent materials.

[0017] The specific applications are as follows:

[0018] The preparation method of the fluorescent material comprises the following steps: adding 10-15g of the above-mentioned combined metal complex into 80-120mL of cellulose solution, and ultrasonically treating for 20-40min; conducting a closed reaction at 100-120°C for 10-16h, cooling to room temperature and filtering, adding 3-6g of phase change material into the filter cake, grinding and mixing evenly, and vacuum drying to obtain the fluorescent material.

[0019] Preferably, the microcrystalline cellulose is prepared by dissolving 2-5 g of microcrystalline cellulose in 100 mL of 1-5 wt % hydrochloric acid.

[0020] Preferably, the ultrasonic parameters are: power 400W, ultrasonic frequency 20kHz.

[0021] Preferably, the phase change material is any one of polyethylene glycol 20000, paraffin, and stearic acid. Most preferably, the phase change material is polyethylene glycol 20000.

[0022] Paraffin, stearic acid, and polyethylene glycol 20000 all have good stability at high temperatures and can play a certain protective role. However, polyethylene glycol 20000 is significantly better than paraffin and stearic acid. The reason is that paraffin and stearic acid mainly interact with fluorescent materials through van der Waals forces, which are relatively weak and easily destroyed at high temperatures. Polyethylene glycol contains a large number of ether bonds and hydroxyl groups in its molecular structure. These functional groups can form hydrogen bonds or other weak interactions with molecules in fluorescent materials. This interaction can enhance the stability of fluorescent materials and improve their heat aging resistance.

[0023] Beneficial effects of the present invention:

[0024] Compared with the prior art, the combined metal complex of the present invention selects 2-hydroxy-3-methoxybenzoic acid with a multi-coordination mode and a fluorescence emission at 380-550nm as an organic ligand, which can enrich the luminescent color and improve the quantum yield; the long fluorescence lifetime is beneficial to time-resolved fluorescence imaging and the fluorescence effect after 3D printing; the good thermal stability ensures the performance and durability of the material under different environmental conditions; and the environmentally friendly characteristics meet the requirements of sustainable technology and green chemistry. DETAILED DESCRIPTION

[0025] The parameters and sources of some substances in the examples are as follows:

[0026] 2-Hydroxy-3-methoxybenzoic acid, CAS number: 877-22-5.

[0027] Microcrystalline cellulose, particle size 50 μm, model SH-CG1, sourced from Anhui Shanhe Pharmaceutical Excipients Co., Ltd.

[0028] Example 1

[0029] A combined metal complex is prepared by mixing a 4f metal complex [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O and a 4f metal complex [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O in a mass ratio of 1:1.

[0030] The preparation method of the 4f metal complex [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O is as follows: 68 mg of 2-hydroxy-3-methoxybenzoic acid and 116 mg of triethylamine are dissolved in 2.25 mL of N,N-dimethylformamide; then 135 mg of Dy(NO3)3·6H2O is dissolved in 2.25 mL of distilled water; the above solutions are mixed and then stirred for 2 hours; and the filtrate is volatilized at room temperature to obtain block-shaped square colorless crystals.

[0031] The preparation method of the 4f metal complex [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O is as follows: 68 mg of 2-hydroxy-3-methoxybenzoic acid and 131 mg of triethylamine are dissolved in 2 mL of N,N-dimethylformamide; then 365 mg of Dy(NO3)3·6H2O is dissolved in 4 mL of distilled water; the above solutions are mixed and then stirred for 2 hours; after the solution is naturally evaporated in the air, rectangular block-shaped colorless crystals are obtained.

[0032] Example 2

[0033] A method for preparing a fluorescent material is as follows: adding 12 g of the combined metal complex prepared in Example 1 to 100 mL of a cellulose solution, ultrasonically mixing for 30 min, with ultrasonic parameters as follows: power 400 W, ultrasonic frequency 20 kHz; adding to a closed reactor and reacting at 105° C. for 12 h, cooling to room temperature and filtering, and vacuum drying the filter cake at 80° C. to constant weight to obtain the fluorescent material.

[0034] The cellulose solution is prepared by dissolving 3 g of microcrystalline cellulose in 100 mL of 2 wt % hydrochloric acid.

[0035] Example 3

[0036] A method for preparing a fluorescent material is as follows: adding 12 g of the combined metal complex prepared in Example 1 to 100 mL of a cellulose solution, ultrasonically mixing for 30 min, with ultrasonic parameters as follows: power 400 W, ultrasonic frequency 20 kHz; adding to a closed reactor and reacting at 105° C. for 12 h, cooling to room temperature and filtering, adding 4 g of polyethylene glycol 20000 to the filter cake, grinding and mixing evenly, and vacuum drying at 80° C. to constant weight to obtain the fluorescent material.

[0037] The cellulose solution is prepared by dissolving 3 g of microcrystalline cellulose in 100 mL of 2 wt % hydrochloric acid.

[0038] Example 4

[0039] A method for preparing a fluorescent material is as follows: adding 12 g of the combined metal complex prepared in Example 1 to 100 mL of a cellulose solution, ultrasonically mixing for 30 min, with ultrasonic parameters as follows: power 400 W, ultrasonic frequency 20 kHz; adding to a closed reactor and reacting at 105° C. for 12 h, cooling to room temperature and filtering, adding 4 g of paraffin wax to the filter cake, grinding and mixing evenly, and vacuum drying at 80° C. to constant weight to obtain the fluorescent material.

[0040] The cellulose solution is prepared by dissolving 3 g of microcrystalline cellulose in 100 mL of 2 wt % hydrochloric acid.

[0041] Example 5

[0042] A method for preparing a fluorescent material is as follows: adding 12 g of the combined metal complex prepared in Example 1 to 100 mL of a cellulose solution, ultrasonically mixing for 30 min, with ultrasonic parameters as follows: power 400 W, ultrasonic frequency 20 kHz; adding to a closed reactor and reacting at 105° C. for 12 h, cooling to room temperature and filtering, adding 4 g of stearic acid to the filter cake, grinding and mixing evenly, and vacuum drying at 80° C. to constant weight to obtain the fluorescent material.

[0043] The cellulose solution is prepared by dissolving 3 g of microcrystalline cellulose in 100 mL of 2 wt % hydrochloric acid.

[0044] Test Example 1

[0045] The fluorescence lifetime of the combined metal complex / fluorescent material of the embodiment was tested using a photoelectric integrated time-resolved spectrometer with an excitation wavelength of 365 nm.

[0046] The combined metal complex / fluorescent material of the embodiment was kept at 200° C. for 10 minutes and then cooled to room temperature, and the fluorescence lifetime test was performed again. The excitation wavelength was 365 nm.

[0047] Table 1

[0048]

[0049]

[0050] Fluorescent materials are increasingly used in contemporary science and industry, especially in 3D printing, where they provide unique visual effects and functional properties. In the manufacturing process of 3D printing filaments, the mixed extrusion of fluorescent materials with plastic raw materials and other additives is carried out under high temperature conditions. Fluorescent materials should maintain the stability of their chemical structure at high temperatures without decomposition or discoloration. This means that the active ingredients in fluorescent materials need to remain stable within the processing temperature range. During long-term high-temperature processing, fluorescent materials should not experience performance degradation, such as reduced brightness or color changes. Therefore, by testing the fluorescence lifetime of fluorescent materials before and after high temperature, its heat aging resistance can be well judged.

[0051] From Table 1, it can be seen that the fluorescence lifetime of the fluorescent materials of Examples 2-5 is significantly longer than that of the combined metal complex of Example 1. The reason may be that the unique molecular structure and properties of cellulose may interact with the combined metal complex. This interaction may cause energy to be transferred from cellulose to the metal complex, or form a certain energy transfer channel between the two, thereby extending the fluorescence lifetime of the fluorescent material.

[0052] Moreover, by comparing Examples 3-5, it can be found that the heat aging resistance of the fluorescent material of Example 3 is significantly better than that of Examples 4-5. Although paraffin and stearic acid both have good stability at high temperatures and can play a certain protective role. However, paraffin and stearic acid mainly interact with the fluorescent material through van der Waals forces, and this interaction is relatively weak and easily destroyed at high temperatures. The polyethylene glycol molecular structure contains a large number of ether bonds and hydroxyl groups, and these functional groups can form hydrogen bonds or other weak interactions with the molecules in the fluorescent material. This interaction can enhance the stability of the fluorescent material and improve its heat aging resistance.

[0053] Test Example 2

[0054] The 3D printing wire is prepared according to the following process: 100 parts by weight of polylactic acid and 2 parts by weight of fluorescent material are added to a mixer, and mixed for 10 minutes at a mixer speed of 300 r / min to obtain a mixed material; the obtained mixed material is extruded into a filament and rolled up through a 3D printing consumable single screw extruder, and the extrusion temperature is controlled at 200°C; and the 3D printing wire is obtained. The fluorescent materials are the combined metal complex and the fluorescent material in the embodiment.

[0055] Extrusion test: Load the prepared 3D printing filament into the 3D printer and perform an automatic extrusion test through a 0.4mm printing nozzle. Keep printing and record the length when blockage or breakage occurs. If it exceeds 10000mm (100m) without blockage or breakage, the test is terminated. (Each fluorescent material is tested 3 times and the average value is taken)

[0056] Table 2

[0057] Length without blockage or breakage Example 1 4752 Example 2 5322 Example 3 7716 Example 4 6098 Example 5 5967 Control group: polylactic acid wire 5608

[0058] In the actual application of fluorescent materials, when the thermal stability of fluorescent materials is poor, they may decompose or change their properties under high temperature, resulting in uneven internal dispersion of the processed wire, which can easily lead to clogging during the printing process. It is also possible that the addition of fluorescent materials may cause the viscosity of the printing material to change, resulting in poor flow and clogging.

[0059] Through the detailed comparison between Example 1 and Example 2, it can be clearly found that when the metal complex in Example 1 is fixed by cellulose, and the fluorescent material prepared is applied to the polylactic acid wire for 3D printing, the printing performance of the wire can be effectively improved. Specifically, this specially treated fluorescent material can significantly reduce the possibility of nozzle clogging during 3D printing. In Example 1, the length of the combined metal complex when no blockage or breakage occurs during the extrusion test is 4752mm. In Example 2, the fluorescent material obtained by fixing the combined metal complex with cellulose is applied to the polylactic acid wire, and its length when no blockage or breakage occurs reaches 5322mm. The change in this data fully illustrates that the fluorescent material prepared by fixing the metal complex with cellulose has a positive effect on improving the printing performance of 3D printing wires, and can provide a more stable and reliable material guarantee for the 3D printing process, reduce the risk of printing interruption caused by nozzle clogging, and improve printing efficiency and quality.

[0060] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A combined metal complex, characterized in that: It includes at least one of 4f metal complexes [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O and 4f metal complexes [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O.

2. The combined metal complex according to claim 1, characterized in that: The 4f metal complex [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O and the 4f metal complex [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O are mixed in a mass ratio of 1-3:1-3.

3. The combined metal complex according to claim 1 or 2, characterized in that: The preparation method of the 4f metal complex [Dy3(HMBA)(MBA)3(H2O)3(OH)2]·10H2O is as follows: 40-80 mg of 2-hydroxy-3-methoxybenzoic acid and 100-150 mg of triethylamine are dissolved in 2-3 mL of N,N-dimethylformamide; then 100-150 mg of Dy(NO3)3·6H2O is dissolved in 2-3 mL of distilled water; the above solutions are mixed and then stirred for 1-3 hours; and the filtrate is volatilized at room temperature to obtain block-shaped square colorless crystals.

4. The combined metal complex according to claim 1 or 2, characterized in that: The preparation method of the 4f metal complex [Dy6(MBA)6(OH)4(H2O)8](OH)2·33H2O is as follows: 40-80 mg of 2-hydroxy-3-methoxybenzoic acid and 100-150 mg of triethylamine are dissolved in 1-3 mL of N,N-dimethylformamide; then 300-400 mg of Dy(NO3)3·6H2O is dissolved in 3-6 mL of distilled water; the above solutions are mixed and then stirred for 1-3 hours; after the solution is naturally evaporated in the air, rectangular block-shaped colorless crystals are obtained.

5. Use of the combined metal complex as claimed in any one of claims 1 to 4 in fluorescent materials.

6. The use according to claim 5, characterized in that The preparation method of the fluorescent material comprises the following steps: adding 10-15g of the combined metal complex according to any one of claims 1-4 to 80-120mL of cellulose solution, and ultrasonically treating for 20-40min; conducting a closed reaction at 100-120°C for 10-16h, cooling to room temperature and filtering, adding 3-6g of phase change material to the filter cake, grinding and mixing evenly, and vacuum drying to obtain the fluorescent material.

7. The use according to claim 6, characterized in that: The cellulose solution is prepared by dissolving 2-5 g of microcrystalline cellulose in 100 mL of 1-5 wt % hydrochloric acid.

8. The use according to claim 6, characterized in that The ultrasonic parameters were: power 400 W, ultrasonic frequency 20 kHz.

9. The use according to claim 6, characterized in that: The phase change material is any one of polyethylene glycol 20000, paraffin and stearic acid.

10. The use according to claim 6, characterized in that: The phase change material is polyethylene glycol 20000.

Citation Information

Patent Citations

  • Preparation of 3d printing composite material by use of PLA matrix capable of generating fluorescence

    CN109721979A

  • Double-wavelength fluorescent anti-counterfeiting fiber and manufacturing method thereof

    CN110106574A